Composition, structure and similarity of the Phanerogamic Flora of a “brejo de altitude”, Serra de Itacoatiara, Uruburetama Massif, Ceará, Brazil - Diego Santos; Álvaro Nepomuceno; Luana Mateus de Sousa; Ketley Gomes; Swami Costa; Tiago Batista; Maria Iracema Bezerra Loiola; Marlene Feliciano Figueiredo; Elnatan Bezerra de Souza (Rodriguésia)
Abstract The Flora of Brazil is currently considered the richest in the world, with 46,087 species of angiosperms, 57.04% of which are endemic. The country has two biodiversity hotspots: the Atlantic Forest and the Cerrado, where the biodiversity was previously considered a third lower than the scientific community currently estimates. The country demands urgent efforts to get to know its flora, and research in the area of floristics should continue, in order to provide data on plant diversity for the recognition and preservation of Brazilian flora. The “brejos de altitude” (tropical rainforest) represent one of the centers of endemism in the Atlantic Forest and are present in five states of the Northeastern region, specifically on mountain peaks in geological massifs. Their biodiversity is threatened mainly by agricultural activities and the introduction of exotic species. Considering the importance of floristic knowledge for the conservation of flora in the “brejos de altitude”, the present work aimed to carry out the floristic survey of the “brejo de altitude” located in Pico de Itacoatiara, Maciço de Uruburetama, and to evaluate its floristic similarity with the flora of other “brejos de altitude” in the Northeastern region.